Jumping Height Does Not Increase in Well Trained Volleyball Players After Transcutaneous Spinal Direct Current Stimulation - Jadczak, Łukasz; Wieczorek, Andrzej; Grześkowiak, Marcin; Wieczorek, Jacek; Łochyński, Dawid (Frontiers in Physiology, 2019)
Transcutaneous spinal direct current stimulation (tsDCS) increases corticospinal and spinal reflex excitability, and may be a new tool for increasing muscle explosive performance in sports training. The aim of the study was to evaluate whether tsDCS can enhance jumping ability in trained humans practicing volleyball. Twenty eight participants completed the study, including 21 men and 7 women. We investigated the effects of a single 15-minute session of sham, anodal, and cathodal tsDCS over spine and shoulder on repeated counter movement jump (CMJ) and squat jump (SJ) performance at 0, 30 and 60 minutes post-stimulation. The order of SJs and CMJs sets in each session was randomized. In each SJ and CMJ set consisted of 3 jumps. The break between each attempt was 1 minute and the interval between the sets was 3 minutes. Two-way repeated measures ANOVA did not show effect of time, nor stimulation method, nor stimulation method × time interactions on SJ (time: F(1.8, 142.1)=1.054; p=0.346, stimulation: F(2, 78)=0.019; p=0.981, stimulation × time: F(3.6, 142.1)=0.725;p=0.564) or CMJ (time: F(1.8, 140.9)=2.092; p=0.132, stimulation: F(2, 78)=0.005; p=0.995, stimulation × time: F(3.6, 140.9)=0.517; p=0.705) performance. Single session of tsDCS over spine and shoulder does not increase jumping height in well-trained volleyball players. This is an important finding for coaches and strength conditioning professionals for understanding the practical utility of tsDCS for enhancing muscular explosiveness.